Flexible dentures, a questionable decision as a prosthetic alternative in dentistry: a literature review - San Martin Andrade, Daniela (2021)
The present review aims to determine the characteristics of flexible prostheses and their prosthetic alternatives, for this, the PubMed, SciELO and Scholar google databases were used and the following keywords were used: flexible prosthesis, “valplast” and nylon prosthesis. A total of 30 articles were collected in English, Spanish and Portuguese languages. It was determined that flexible type removable prostheses (nylon) are characterized by their elasticity and ease of adopting colors, improving their aesthetics, unfortunately the material that makes them up does not seem to meet all the desired properties in the long term. Its use can be implemented as long as it is temporarily.